2015
DOI: 10.1007/s10620-014-3463-1
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Promotes Gastric Cancer Cell Invasion and Migration Via ST2–ERK1/2 Pathway

Abstract: IL-33 promotes gastric cancer cell invasion and migration by stimulating the secretion of MMP-3 and IL-6 via ST2-ERK1/2 pathway. Thus, IL-33 may be a useful marker for the diagnosis and treatment of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 27 publications
2
77
1
2
Order By: Relevance
“…Considering the disparity that exists in dialysis practice across different regions and introduction of new treatment modalities, the results obtained from this single-center study require validation in external population. Second, it is clear that IL-33/ST2 signaling participates in the immune response of numerous diseases, such as rheumatoid arthritis [27] , asthma [28] , malignancy [29,30] and vasculitis [31] . Underlying malig-nancy and immune alteration in study participants may be potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the disparity that exists in dialysis practice across different regions and introduction of new treatment modalities, the results obtained from this single-center study require validation in external population. Second, it is clear that IL-33/ST2 signaling participates in the immune response of numerous diseases, such as rheumatoid arthritis [27] , asthma [28] , malignancy [29,30] and vasculitis [31] . Underlying malig-nancy and immune alteration in study participants may be potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck squamous cell carcinoma (HNSCC), it has been shown that administration of IL-33 promoted cancer cell migration and invasion through induction of epithelial-mesenchymal transition [97]. Recently, it has been suggested that IL-33 can promote gastric cancer cell invasion and migration, which was suggested to be mediated by activation of ERK1/2 [98]. Other studies, however, have shown divergent anti-tumorigenic effects of IL-33 and ST2 in cancer.…”
Section: "Wounds That Do Not Heal" -Understanding the Role Of Il-33 Imentioning
confidence: 99%
“…Some authors have reported that IL-33 promotes metastasis of gastric (Yu et al, 2015) and colorectal cancers. However, other papers have reported that IL-33 may act as an adjuvant to enhance antigen-specific tumor immunity .…”
Section: Il-33 In Autoimmune and Inflammatory Disordersmentioning
confidence: 99%